Herbs and Spices - Akram, Muhammad; Shabir Ahmad, Rabia; Akram, Muhammad; Shabir Ahmad, Rabia (IntechOpen, 2020)
This edited volume, (3z(BHerbs and Spices(3y(B, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of agricultural and biological sciences. The book comprises single chapters authored by various researchers and edited by an expert active in the medical research area. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on herbs and spices, and opening new possible research paths for further novel developments.s
English
Keywords: Pharmacology; Pharmacology